1974
DOI: 10.1111/j.1476-5381.1974.tb08581.x
|View full text |Cite
|
Sign up to set email alerts
|

A Central Vasodepressor Effect of Dyflos

Abstract: 1 Cats were anaesthetized with pentobarbitone sodium and atropinized peripherally by intravenous injection of atropine methyl nitrate; the effect was examined of topical bilateral application of dyflos to the ventral surface of the medulla oblongata at a region lateral to the pyramids and caudal to the trapezoid bodies. Dyflos was applied by means of perspex rings; the volume of fluid placed in each ring was 10 gl.2 The topical application of dyflos (1-20 mg/ml) produced a fall in arterial blood pressure witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The persistence of the hypotensive action of oxotremorine following decerebration and its absence in spinal cats suggests a site of action in the brain stem. This is consistent with the observations of Guertzenstein (1973) and Edery & Guertzenstein (1974) that carbachol decreased blood pressure when applied locally to a discrete area on the ventral surface of the brain stem.…”
Section: Discussionsupporting
confidence: 92%
“…The persistence of the hypotensive action of oxotremorine following decerebration and its absence in spinal cats suggests a site of action in the brain stem. This is consistent with the observations of Guertzenstein (1973) and Edery & Guertzenstein (1974) that carbachol decreased blood pressure when applied locally to a discrete area on the ventral surface of the brain stem.…”
Section: Discussionsupporting
confidence: 92%
“…As the bilateral area from which vasopressin release was obtained with nicotine lies 6-9 mm caudal to the trapezoid bodies the area is situated more caudally on the ventral surface of the medulla than the bilateral area from where most of the blood pressure effects have been obtained with drugs topically applied through perspex rings (Feldberg & Guertzenstein, 1972;Guertzenstein, 1973;Bousquet & Guertzenstein, 1973;Edery & Guertzenstein, 1974;Guertzenstein & Silver, 1974). For pentobarbitone sodium, glycine and clonidine, it was shown that they no longer produced their depressor effects with the rings placed so that their rostral border was 5 mm caudal from the trapezoid bodies, and the glycine-sensitive area was restricted in longitudinal direction to between 1 and 2.5 mm caudal to the trapezoid bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that a number of drugs which, on intraventricular injection affect blood pressure, heart rate, respiration or blood glucose, act in this way (Feldberg & Guertzenstein, 1972;Guertzenstein, 1973;Bousquet & Guertzenstein, 1973;Edery & Guertzenstein, 1974;Feldberg & Gupta, 1974;Guertzenstein & Silver, 1974;Dey, Feldberg & Wendlandt, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Previously it was shown that a number of drugspentobarbitone sodium, glycine, clonidine, physostigmine, dyflos and carbacholproduced a fall in arterial blood pressure in anaesthetized cats when applied topically to the ventral surface of the brain stem through paired Perspex rings placed across the medulla. These depressor effects were obtained when the areas covered by the rings had their uppermost limits just, and their lowest limits about 4 mm, caudal to the trapezoid bodies (Feldberg & Guertzenstein, 1972;Guertzenstein, 1973;Bousquet & Guertzenstein, 1973;Edery & Guertzenstein, 1974). These areas are indicated by the ovals A of the diagram of Fig.…”
mentioning
confidence: 92%